Violence of democracy : interparty conflict in South India - Chaturvedi, Ruchi (Durham: Duke University Press, 2023)
"Violence of Democracy examines the rise of majoritarian politics in India through a close examination of a decades-long series of confrontations in the Kannur district of Kerala between members of the Communist Party of India and supporters of two right-wing parties, Rashtriya Swayam Sevak Sangh and Bharatiya Janata Party. Drawing on extensive ethnographic fieldwork in the region, Ruchi Chaturvedi investigates the unique political character of the violent conflict between the 'party left' and the 'Hindu right', which does not correspond neatly to divisions along ethnic, racial, religious, or linguistic lines. The book draws attention to how this partisan conflict is mediated and perpetuated by legitimate institutions of democratic rule, including local trial courts. Although situated in a close examination of the particular nuances of Kerala, Violence of Democracy provides broader insights into the phenomenon of political violence in majoritarian democracies throughout the postcolonial world"--
Containment and cretinism : the early democratic decades -- The CPI (M) and the making of an antagonistic political field -- Care, connectedness, and violence in Hindu right communities -- Law's subterfuge : affording alibis and bolstering conflict -- Individuating responsibility : The problem of intention, injustice, and justice.
Includes bibliographical references and index.
Keywords: Communist Party of India (Marxist); Rashtriya Swayam Sevak Sangh; Bharatiya Janata Party; Political parties -- India -- Kerala; Political violence -- India -- Cannanore (District); Right and left (Political science) -- India -- Kerala; Democracy -- India, South; HISTORY / Asia / South / India; POLITICAL SCIENCE / World / Asian; Kerala (India) -- Politics and government -- 21st century